Historical analysis of double poling in high-level cross-country skiing (xcs) - Canclini, Ar. Canclini, An.; Pozzo, R.; Baroni, G.; Lindinger, S. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
Over the past twenty years there have been at least two generations of skiers who have competed in high-level competitions. Since 1995, our group has recorded and analyzed (through 3-dimensional reconstructions) the performances of the best athletes involved in numerous World Cup races in the various cross-country skiing (XCS) techniques. Therefore, it seemed to be interesting to propose a historical analysis of these observations and 3D reconstructions from race data over at least the last 20 years. In the last years the skating techniques have received more attention from skiers, coaches, and researchers in order to improve the racers' performance. Slightly less studies are conducted as regards in the "older" classical technique. However, the classical technique is used in an half of all World Cup XCS skiing competitions and an elite skier does not lose any opportunity to try to win the overall World Cup. The cross-country skiing technique evolved significantly starting from the '80s (diversification between freestyle and classical techniques races). During the last decade, a renewed interest in the classical technique , especially in double poling has grown, also connected to the Ski Classic and Worldloppet, so called popular races (PRs). Since '80s, new equipments and materials, better ski tracks preparation, improvements in the training methodology and the specific use of upper body segments, emphasized in Skating, enhanced the velocity and the performances in all kinds of races. Moreover, nowadays in the pursuit competitions the athletes perform both techniques in the same competition with a change of material after half distance (e.g. 2 x 1 5 km). Both Classical and Free style races challenge the athletes to master a wide range of speeds and slopes, depending also from the snow friction and the environmental conditions, and to adapt their technique accordingly. Thus, skiers possess different skiing techniques and continuo usly switch among them during a race. Classical style in XCS was the unique technique used until 1984, divided in three main strides: Diagonal stride (DS), Double Pole (DP) and DP with Kick (DPK). Even if the motion actions remained mostly the same, a lot o f changes were found since '90 due to different causes (Holmberg 2005, Rapp 2007, Lindinger, 2007). Actually there are some other special strides as herringbone or tuck.